DKP oscillator in the presence of magnetic field in (1+2)-dimensions for spin-zero and spin-one particles in noncommutative phase space - Hassanabadi, H.; Molaee, Z.; Zarrinkamar, S. (The European physical journal. C, Particles and fields, 2012)
The DKP oscillator in the presence of a magnetic field is solved for spin-zero and spin-one particles in noncommutative phase space in (1+2) dimensions. We obtain the energy eigenvalues and the corresponding wave functions in an exact analytical manner. In addition, we discuss our solutions in various conditions and comment on the critical values of the magnetic field as well as the coinciding points of commutative and noncommutative cases. We include some illustrating figures and numerical data.